(untitled) (Biological Sciences - PJSIR, 1997)
The cyclic voltammetric studies were carried out on platinum and heazlewoodite (Ni3S2) electrodes in 0.1 mol. dm:’ sodium tetra borate buffer with and without sodium diethyldithiocarbamat (DTC) and sodium sulphide (Na2S3) added separately orincombination undercomparable conditions. The combination ofDTC andNa2S andtheeffect of sulphursoproducedonDTCanditsoxidationisdescribed.Flotationexperimentswerealsoconductedtostudytheeffect of Na2S concentration on heazlewoodite recoveries. An increase of about 6% in flotation recovery was observed for addition of 10.4 rnol.dm" N S concentration.